The Role of Auditory Feedback at Vocalization Onset and Mid-Utterance - Scheerer, Nichole E.; Jones, Jeffery A. (Frontiers in Psychology, 2018)
Auditory feedback plays an important role in monitoring and correcting for errors during speech production. Previous research suggests that at vocalization onset, auditory feedback is compared to a sensory prediction generated by the motor system to ensure the desired fundamental frequency (F0) is produced. After vocalization onset, auditory feedback is compared to the most recently perceived F0 in order to stabilize the vocalization. This study aimed to further investigate whether after vocalization onset, auditory feedback is used strictly to stabilize speakers’ F0, or if it is also influenced by the sensory prediction generated by the motor system. Event-related potentials (ERP) were recorded while participants produced vocalizations and heard the F0 of their auditory feedback perturbed suddenly mid-utterance by half a semitone. For half of the vocalizations, at vocalization onset, participants’ F0 was also raised by half a semitone. Thus, half of the perturbations occurred while participants heard their unaltered auditory feedback, and the other half occurred in auditory feedback that had also been perturbed 50 cents at vocalization onset. If after vocalization onset auditory feedback is strictly used to stabilize speakers’ F0, then similarly sized vocal and ERP responses would be expected across all trials, regardless of whether the perturbation occurred while listening to altered or unaltered auditory feedback. Results indicate that the perturbations to the participants’ unaltered auditory feedback resulted in larger vocal and N1 and P2 ERP responses than perturbations to their altered auditory feedback. These results suggest that after vocalization onset auditory feedback is not strictly used to stabilize speakers’ F0, but is also used to ensure the desired F0 is produced.